Pengaruh Literasi Perpajakan, Pelayanan Fiskus dan Modernisasi Pembayaran Pajak Terhadap Tingkat Kepatuhan Formal Wajib Pajak Orang Pribadi - Agustina Cindiana Laisa Putri; Fitri Handayani; Latersia Br Gurusinga (Benefit: Journal of Bussiness, Economics, and Finance, 2026)
This research uses a quantitative approach and aims to estimate and examine the partial effect of Tax Literacy, Tax Officer Services, and the Modernization of Tax Payment on the Formal Compliance Level of Individual Taxpayers at the KPP Pratama Medan Timur. The sample used consisted of 100 taxpayers selected using the Slovin formula. The results of this study indicate that, partially, Tax Literacy has a positive and significant effect on the Formal Compliance Level of individual taxpayers. Tax Officer Services do not have a positive and significant effect on the Formal Compliance Level of individual taxpayers, and the Modernization of Tax Payment also does not have a positive and significant effect on the Formal Compliance Level of individual taxpayers. This research is important in understanding the regulations concerning taxpayers.